Buenas noches, construcción, buenas noches, diversión [book with audioplayer] - Rinker, Sherri Duskey ([Library Ideas, LLC], 2022)
At sunset, when their work is done for the day, a crane truck, a cement mixer, and other pieces of construction equipment make their way to their resting places and go to sleep.